Angiogenic Effects of Collagen/Mesoporous Nanoparticle Composite Scaffold Delivering VEGF165. (5th September 2016) - Kim, Joong-Hyun; Kim, Tae-Hyun; Kang, Min Sil; Kim, Hae-Won
Abstract : Vascularization is a key issue for the success of tissue engineering to repair damaged tissue. In this study, we report a composite scaffold delivering angiogenic factor for this purpose. Vascular endothelial growth factor (VEGF) was loaded on mesoporous silica nanoparticle (MSN), which was then incorporated within a type I collagen sponge, to produce collagen/MSN/VEGF (CMV) scaffold. The CMV composite scaffold could release VEGF sustainably over the test period of 28 days. The release of VEGF improved the cell proliferation. Moreover, the in vivo angiogenesis of the scaffold, as studied by the chick chorioallantoic membrane (CAM) model, showed that the VEGF-releasing scaffold induced significantly increased number of blood vessel complexes when compared with VEGF-free scaffold. The composite scaffold showed good biocompatibility, as examined in rat subcutaneous tissue. These results demonstrate that the CMV scaffold with VEGF-releasing capacity can be potentially used to stimulate angiogenesis and tissue repair.